PENGARUH EDUKASI KESEHATAN MELALUI MEDIA SOSIAL LINE TERHADAP SIKAP REMAJA PUTRI TENTANG PENCEGAHAN ANEMIA DEFISIENSI BESI DI SMP NEGERI 2 RENDANG - Dewi, Ni Putu Tri Purnama; Susila, I Made Dwie Pradnya; Arisudhana, Gede Arya Bagus (Poltekkes Kemenkes Medan, 2021)
Girls adolescent are in high risk of developing anemic. The high prevalence of the girl adolescents, proves that the low awareness of iron deficiency anemia. Education is one way to increase respondents' knowledge so that they can form positive attitudes and healthy behaviors. Social media can be used as an educational media that is quite effective in reaching young people. The purpose of this study was to determine the effect of health education through social media Line on the attitudes of adolescents about the prevention of iron deficiency anemia in SMP Negeri 2 Rendang. The research method used was quantitative pre-experimental design with One Group Pretest and Posttest Design. The population in the study were young women class VIII and XI in SMP Negeri 2 Rendang in the school year 2019/2020 with a sample of 105 students selected based on simple random sampling. Respondents received education twice a week for 5 weeks. The results showed that the attitudes of girl adolescents before being given education in sufficient category of 89.5% and after being given education was in good category of 19%. From the Wilcoxon sign rank test statistical results obtained Zhitung = 6,151> Ztable = 1,645 P value = 0,000 <? 0.05. it can be concluded that education through social media line can influence the attitudes of girl adolescents about the prevention of iron deficiency anemia.